EXPERIENCE OF EUROPEAN AND ASIAN STATES IN THE REGULATION OF TRANSBOUNDARY RIVERS (Journal of actual problems of jurisprudence, 2020)
Abstract. This article discusses the issues of legal regulation of the rational use of transboundaryrivers and reservoirs, as well as the problems of improving the water legislation of the Republic ofKazakhstan in the context of globalization and integration. The issues of water supply and pollution ofwater resources go beyond purely national problems and need to be addressed at the international level.Kazakhstan has many common watercourses with several countries, the management of which involvesthe search for compromises. Complex cross-border problems have accumulated and need to be resolvedtaking into account not only the interests of both States, but also the preservation of natural ecosystemscapable of performing their ecological functions in the region and ensuring environmental security. Theproblem of small rivers, which are of great value for the preservation of river ecosystems, is raised.The author comes to the conclusion that many years of experience in solving the problems of transboundaryrivers shows that only based on the unity of legal principles, mutual respect and respect foreconomic and political interests, it is possible to ensure regional stability, and to solve the problems ofsharing and protection from pollution of water resources of transboundary rivers. The creation of a legalbasis for water resources management will allow to resolve the existing contradictions in the use of waterresources in the future.Key word: transboundary rivers, water bodies, regulation, water law, water resources, water use,water bodies.